Regioselective C 2 sulfonylation of indoles mediated by molecular iodine - Praewpan Katrun (2018)
A facile and general method for regioselective C2 sulfonylation reaction of indoles mediated by iodine is described. The 2-sulfonylated products were obtained up to 96% yield under mild reaction conditions (room temperature, 2 h). © 2014 American Chemical Society.